A mini-review on different polymerization protocols for resin-based dental composites - Sorrentino, Edoardo; Della Rocca, Ylenia; Marconi, Guya Diletta; Iezzi, Giovanna; Trubiani, Oriana; D’Arcangelo, Camillo; De Angelis, Francesco; Diomede, Francesca (Italian Journal of Anatomy and Embryology, 2023)
Biocompatibility is one of the major prerequisites for safe clinical application of materials. Dental resin composites may release their components into oral environment, which can lead to adverse reactions. Several studies have identified that many organic components of composites resin, such as bisphenol-A-glycidyl-methacrylate (Bis-GMA), triethylene glycol dimethacrylate (TEGDMA), urethane dimethacrylate (UDMA) and 2-hydroxyethyl methacrylate (HEMA) show a cytotoxic profile. Cytotoxicity is mainly sustained by free monomers released after polymerization process. Direct restorations are polymerized at body temperature by visible light emitting lamps, but the conversion from monomer to polymer after light-curing is never complete. To improve the degree of conversion of resin-based composites, additional curing protocols performed at increased temperatures, such as heat-curing, can be employed. Polymerization reaction plays a key role in the conversion of the free monomers into polymers and resin-based composites with high degree of conversion might show higher biocompatibility. The aim of this mini-review is to report current knowledge about the cytotoxicity of different composite resins, cured in two different ways. Further studies are necessary to better understand the relationship between the cytotoxicity and the degree of polymerization of resin-based composites.